Implementasi Arsitektur Firewall Sebagai Sistem Keamanan Jaringan Wifi 802.11ax Aruba Software Defined Wan (SD-Wan) - Syamsu, Muhajir; Widodo, Widodo (Jurnal Teknologi Informasi (JUTECH), 2022)
The concept of WLAN technology continues to evolve so as to be able to keep up with the increasing number of user densities, schemes with density Access Point (AP) and User Stations (STA), IEEE 802.11 creates an IEEE 802.11ax (TGax) to develop a set of physical layer specifications (PHY) and Media Access New Control (MAC). IEEE 802.11ax is called a high efficiency WLAN (HE). currently in the concept of its application in the implementation of the firewall architecture on the 802.11ax WIFI network security system. This study aims to determine the concept of an 802.11ax Wifi network security system architecture developed by Aruba with the latest Access Point system that is able to support the latest Wi-Fi standards and is a wireless Access Point product that may be the first to get Wi-Fi Alliance (WFA) certification in Indonesia. the field of the latest WPA3 and Enhanced Open security system standards, and can provide much stronger encryption services and have simpler IoT security configuration settings. This research uses the literature method where the researcher collects data - information data related to the subject of the research conducted by the researcher. As well as using the data analysis technique used is using content analysis in the form of written documentation and organizing data into categories, describing it into units, what is meant by data analysis techniques. The results of this study.